Factors Influencing Gen Z’s Adoption and Usability on Internet of Things (Iots) in Higher Education: Case of Botswana - Monageng, Thapelo; Rafifing, Neo; Mabina, Alton (COMPETITIVE: Journal of Education, 2025)
The integration of the Internet of Things (IoT) in higher education presents significant opportunities to enhance learning experiences and institutional operations. However, the adoption and effective utilization of IoT technologies among Generation Z (Gen Z) students in Botswana's higher education sector remain underexplored. This study investigates the factors influencing IoT adoption and usability among Gen-Z students in Botswana's higher education institutions, with a specific focus on the role of social media in shaping perceptions and decision-making processes. Employing a mixed-methods approach, the study collected quantitative data through surveys from one hundred participants and qualitative insights through semi-structured interviews with twenty participants. Quantitative analysis revealed that entertainment and information gathering are primary motives for social media engagement, while trust in online content varies across demographics, and encounters with misinformation are common. Qualitative findings highlighted the role of peer validation and algorithm-driven content in shaping opinions. The findings reveal that social media significantly influences students’ awareness, trust, and attitudes toward IoT technologies, with exposure to misinformation and peer validation playing critical roles. Additionally, the study highlights the importance of digital literacy and ethical content moderation in fostering responsible IoT engagement. The results underscore the need for targeted strategies to promote IoT acceptance and digital literacy, ultimately enhancing the quality and effectiveness of technology-enabled learning in Botswana’s higher education sector. This research provides valuable insights for educators, policymakers, and technology developers aiming to facilitate the responsible integration of IoT in higher education.